Comprehensive physiological, transcriptomic, and metabolomic analyses revealed the regulation mechanism of evergreen and cold resistance of Pinus koraiensis needles - Yan Li; Xin Li; Dan Peng; Jiaxin Luo; Shuai Zhu; Haibo Du; Xiaoning Li; Jiafeng Zhang; Jun Meng; Xiaona Pei; Xiyang Zhao (BMC Plant Biology)
Abstract As a significant fruit and timber tree species among conifers, Pinus koraiensis remains it evergreen status throughout the harsh winters of the north, a testament to its intricate and prolonged evolutionary adaptation. This study delves into the annual trends of physiological indicators, gene expression levels, and metabolite accumulation to dissect the seasonal adaptability of P. koraiensis needles. Chlorophyll content reaches its zenith primarily between July and September, whereas carotenoids persist until spring. Additionally, notable seasonal variations are observed in the levels of soluble sugar and protein. Transcriptome data is categorized into four distinct stages: spring (S2), summer (S3-S4), autumn (S5), and winter (S6-S1). The differential expression of transcription factor genes, including bHLH, MYB-related, AP2/ERF, C3H, and NAC, provides insights into the needles’ seasonal adaptations. Analysis of chlorophyll and carotenoid metabolism, sugar metabolism, and the MAPK signaling pathway identifies PSY5 (Cluster-50735.3), AMY13 (Cluster-37114.0), pgm1 (Cluster-46022.0), and MEKK1-1 (Cluster-33069.0) may as potential key genes involved in sustaining the needle’s evergreen nature and cold resistance. Ultimately, a comprehensive annual adaptability map for P. koraiensis is proposed, enhancing understanding of its responses to seasonal variations.